Urbanising cholera : the social determinants of its re-emergence - Dasgupta, Rajib (Hyderabad, [India] : Orient BlackSwan, 2012)
Study focuses on Delhi, India.
Originally presented as the author's thesis (doctoral)--Jawaharlal Nehru University.
Includes bibliographical references (pages 315-331) and index.
Keywords: CHOLERA -- India -- Delhi -- History; URBAN HEALTH -- India -- Delhi -- History